Outcomes of conservative treatment of giant omphaloceles with dissodic 2% aqueous eosin: 15 years' experience - B. D. Kouame; T. H. Odehouri Koudou; J. B. Yaokreh; M. Sounkere; S. Tembely; K. G. S. Yapo; R. Boka; M. Koffi; A. G. Dieth; O. Ouattara; A. da Silva; R. Dick (Wolters Kluwer Medknow Publications, 2014)
Background: The surgical management of giant omphalocele is a surgical challenge with high mortality and morbidity in our country due to the absence of neonatal resuscitation. This study evaluates conservative management of giant omphalocele with dissodic 2% aqueous eosin. Materials and Methods: In the period from January 1997 to December 2012, giant omphaloceles were treated with dissodic 2% aqueous eosin. The procedure consisted of twice a day application of dissodic 2% aqueous eosin (sterile solution for topical application) on the omphalocele sac. The procedure was taught to the mother to continue at home with an outpatient follow-up to assess epithelialization. We studied the duration of the hospital stay, the learning curve of the procedure by the mother, the complications, the duration and the percentage of complete epithelialization and the mortality. Results: A total of 173 giant omphaloceles had a conservative treatment with dissodic 2% aqueous eosin. The average hospital stay was 21 ± 6 days. The learning curve by the mother of the procedure was 10 ± 3 days. Complications of treatment were intestinal functional occlusion 22% and omphalocele sac infection 18%. The complete epithelialization of the omphaloceles sac after application of dissodic 2% aqueous eosin was 68.5%. Mortality was observed in 25.5%. Conclusion: Conservative treatment of giant omphaloceles by dissodic 2% aqueous eosin is a simple, efficient and a good alternative to surgery. The mother can easily learn its procedure which reduces the duration of hospital stay.